The fascination of the talking drums - Chislett, W. A. (International Library of African Music, 1954)
Most people who read stories about Africa and less advanced students of African history (among which I number myself) will be surprised to learn that the sending of messages over long distances by relays of drums is confined to quite a narrow belt of country. It is true that in many parts of Africa, as in many other parts of the world, information is sent by pre-arranged signals and that drums are among the instruments used for this purpose. But the “talking drums” are confined to a narrow strip of Equatorial Africa along the banks of the River Congo and its chief tributaries. Here there are no pre-arranged codes. The drums are made to produce sounds suggested by words in the local language.
Keywords: Talking drum; African Music; Equatorial Africa; River Congo